1996
DOI: 10.1128/jb.178.14.3991-3995.1996
|View full text |Cite
|
Sign up to set email alerts
|

Basic amino acid transport in plasma membrane vesicles of Penicillium chrysogenum

Abstract: The characteristics of the basic amino acid permease (system VI) of the filamentous fungus Penicillium chrysogenum were studied in plasma membranes fused with liposomes containing the beef heart mitochondrial cytochrome c oxidase. In the presence of reduced cytochrome c, the hybrid membranes accumulated the basic amino acids arginine and lysine. Inhibition studies with analogs revealed a narrow substrate specificity. Within the external pH range of 5.5 to 7.5, the transmembrane electrical potential (⌬) functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…These results suggest that the positive side chain of Arg is important for recognition by the transport system. A similar eect has been observed in Arg-transport systems in fungi (Hillenga et al 1996), fungal mitochondria (Yu and Weiss 1992) and in plant vacuoles (Martinoia et al 1991).…”
Section: Discussionmentioning
confidence: 53%
“…These results suggest that the positive side chain of Arg is important for recognition by the transport system. A similar eect has been observed in Arg-transport systems in fungi (Hillenga et al 1996), fungal mitochondria (Yu and Weiss 1992) and in plant vacuoles (Martinoia et al 1991).…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, transportation of chitin and other polysaccharides is not well studied. Previous studies have shown that Penicillium fungi take up and compartmentalize intact amino acids such as glycine and arginine (Kitamoto et al 1988, Hillenga et al 1996 capable of breaking down and absorbing more recalcitrant forms of ON such as the polysaccharide chitin (Binod et al 2007). Penicillium fungi compartmentalize nutrients and amino acids in two main locations: in vacuoles where they can be stored and in cytoplasm where they can be quickly metabolized or transformed (Griffin 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Early observations indicated that uptake of amino acids (Kotyk & Ríhová, 1972), choline (Robson et al, 1992) or saccharides (Kotyk & Höfer, 1965;Deák & Kotyk, 1968) requires energy. Protons were shown to accompany amino acid transport (Eddy et al, 1970;Eddy & Nowacki, 1971;Hillenga et al, 1996). The discovery of an H + -ATPase in N. crassa (Scarborough, 1976) and in yeasts (Villalobo et al, 1981) led to its establishment as the main source of the proton-motive force (PMF) required for uptake of nutrients (Goffeau & Slayman, 1981;Kotyk, 1983).…”
Section: Introductionmentioning
confidence: 99%